Construcción de indicadores sociales y medición de la desigualdad de oportunidades de los cantones Chaguarpamba y Olmedo, año 2012 - CEVALLOS VERDESOTO, MALENA SIBILLY (2016)
Inequality is a subject that arouses great controversy, eradication is difficult and their presence is everywhere. Despite this reality, the political debate on whether it should, how and how much to reduce it, often polarized. Ecuador is a country with high inequality and the cantons and Olmedo Chaguarpamba are no exception as provincial level these are at a disadvantage to other counties such as Loja, Catamayo, among others. Hence the importance of building social indicators and measuring inequality of opportunities and Olmedo Chaguarpamba Cantons. This work seeks to determine what is the level of access for children in cantons Olmedo Chaguarpamba and services regarding education, housing, health TIC'sy?, For it was necessary to start from a baseline (2010) that allows know the value of different indicators of the cantons Chaguarpamba develop and Olmedo giving a starting point for research work. With the use of data representative of households in Chaguarpamba (322) and Olmedo (299) was constructed indicators for education, housing, early childhood TIC'sy whose calculation methodology detailed in the literature review. Furthermore, these indicators are helpful for building IOH, which includes in its measurement, economic indicators, social and anthropometric. In building the IOH, focused on children between the ages of 0 and 16 years for each of the cantons, were analyzed eight times as basic, these were primary culmination of time, attendance, sanitation, electricity, no overcrowding, computers and internet access, chronic malnutrition and immunization, which are being grouped by categories or dimensions, the first two categories formed the HOI for education, the following three dimensions resulted in the HOI for housing, then the next two were the IOH TIC'sy finally the remaining two formed the IOH early childhood. Chaguarpamba and Olmedo share similar characteristics in terms of population, economic and social dynamics, and these are explicit reasons why your IOH by category yielded similar percentages, is the case of the education category and Olmedo Chaguarpamba HOI for 91 , 31% and 5 87.17% respectively, with respect to the level of access to ICT percentage values were obtained for Chaguarpamba 10.72% and 9.50% for the HOI Olmedo and finally presented percentages of Early Childhood 70, 33% and 70.87% Chaguarpamba Olmedo. With respect to the results of the General IOH, it is an average of the HOI by category, in both cantons indicates the presence of inequality rooted mainly in the ICT IOH. The overall percentage difference between cantons IOH is minimal (62.35 Chaguarpamba % and 59.03 Olmedo) and underlies the HOI housing category (77.04% Chaguarpamba and 68.61% Olmedo) as the percentage difference between the two cantons this category is 8.43%, this divergence lies in the opportunities of access to sanitation (66.2% Chaguarpamba and 63.03% Olmedo) and overcrowding (68.67% Chaguarpamba and 58.97% Olmedo). Equal opportunities is part of eradicating inequality and part of the development process and this is where the HOI intervenes, as it becomes a useful diagnostic tool for the analysis of public political focused on reducing inequality.